Survey of high school librarians' salary in Quezon City - Esteban, Amelia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1993)
This research study aims to investigate the salary ranges of private and public high school librarians in Quezon City. Problems in salary condition, school's policy on librarian's salary and position of the library in the organizational structure of the school are included in the objectives as well.
The result of this study will serve as a salary directory of the librarians concerned, a medium to communicate their salary condition, a basis for upgrading their salary and a background for future studies on a more holistic view of the nature of librarians' salary.
The study hypothesizes that : low salary is the prevailing problem that confronts high school librarians and the school's organizational structure affects the policy on librarians' salary. The study follows the methodology of descriptive research design. The subjects are fifty-two chief librarians, professional library staff, and teacher librarians. Questionnaire is the main instrument used in the data gathering.
The data gathered reveal the following : The mode, the highest, and the lowest salary of private high school librarians are P 5,001 to 6,000, P 13,001 and above, and P 2,001 to 3,000, respectively. The highest salary of public high school librarians is P 6,001 to 7,000, and their mode and lowest salaries are both P 3,001 to 4,000.Eighteen librarians, sixteen of them from private schools, have no problem in their salary condition while the rest mainly complain on the small amount of their salary.
Private schools either level the salary of librarians to other employees, usually teachers, or set a fixed amount for librarians' salary. Public schools base the salary of librarians to the National Standardization Law. Librarians in public schools have slower rate of salary increase than those in private schools.
Only ten of the respondents say their library is positioned under the non-academic division. Eight out of this ten receive salary below that of the teachers.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Librarians -- Salaries, pensions, etc. -- Philippines -- Quezon City